Relationship between TRAF6 and deterioration of HCC: an immunohistochemical and in vitro study. Issue 1 (December 2016) - Li, Jian-jun; Luo, Jie; Lu, Jing-ning; Liang, Xiao-na; Luo, Yi-huan; Liu, Yong-ru; Yang, Jie; Ding, Hua; Qin, Gui-hui; Yang, Li-hua; Dang, Yi-wu; Yang, Hong; et al.
Abstract Objective To explore the relationship between tumor necrosis factor receptor-associated factor 6 (TRAF6) and the clinicopathological features in HCC as well as its biological function. Methods Totally, 412 liver tissues were collected, including 171 hepatocellular carcinoma (HCC) and their corresponding non-tumor tissues, 37 cirrhosis and 33 normal liver tissues. The expression of TRAF6 was assessed by immunohistochemistry. Then, analysis of the correlations between TRAF6 expression and clinicopathological parameters in HCC was conducted. Furtherer, in vitro experiments on HepG2 and Hep3B cells were performed to validate the biological function of TRAF6 on HCC cells. TRAF6 siRNA was transfected into HepG2 and Hep3B cell lines and TRAF6 expression was evaluated with RT-qPCR and western blot. The assays of cell viability, proliferation, apoptosis and caspase-3/7 activity were carried out to investigate the effects of TRAF6 on HCC cells with RNA interference. Cell viability was assessed with Cell Titer-Blue kit. Cell proliferation was tested with MTS kit. Cell apoptosis was checked through morphologic detection with fluorescence microscope, as well as caspase-3/7 activity was measured with fluorogenic substrate detection. Results The positive expression rate of TRAF6 protein was 49.7 % in HCC, significantly higher than that of normal liver (12.1 %), cirrhosis (21.6 %) and adjacent non-cancerous tissues (36.3 %, allP  < 0.05). Upregulated TRAF6 was detected in groups with metastasis (Z = −2.058, P  = 0.04) and with low micro-vessel density (MVD) expression (Z = −2.813, P  = 0.005). Spearman correlation analysis further showed that the expression of TRAF6 was positively correlated with distant metastasis (r = 0.158, P  = 0.039) and negatively associated with MVD (r = −0.249, P  = 0.004). Besides, knock-down of TRAF6 mRNA in HCC cell lines HepG2 and Hep3B both resulted in cell viability and proliferation inhibition, also cell apoptosis induction and caspase-3/7 activity activation. Conclusions TRAF6 may contribute to metastasis and deterioration of the HCC via influencing cell growth and apoptosis. Thus, TRAF6 might become a predictive and therapeutic biomarker for HCC.